2021
DOI: 10.21203/rs.3.rs-366930/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Trend of Eight-Years Big Data Analytics of Electronic Medical Records to Review and Study Diagnosis and Treatment of Coronary Artery Disease in Different Genders

Abstract: Background: Cardiovascular Disease (CVD) and Coronary Artery Disease (CAD) in particular, is one of the leading causes of death, morbidity, and mortality in the United States. Notably, women continue to have worse outcomes than men. The causes of these discrepancies have yet to be fully elucidated. The main objective of this study is to detect gender discrepancies in outcome using data analytics to risk stratify ~ 32,000 patients with CAD of the total 960,129 patients treated at UCSF Medical Center during an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Our previous study found significant gender differences in the average waiting days from the first event to diagnostic catheterization [ 4 ]. We did not find significant gender-based differences between diagnostic catheterization and therapeutic cardiac catheterization (Percutaneous Coronary Intervention-PCI).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study found significant gender differences in the average waiting days from the first event to diagnostic catheterization [ 4 ]. We did not find significant gender-based differences between diagnostic catheterization and therapeutic cardiac catheterization (Percutaneous Coronary Intervention-PCI).…”
Section: Resultsmentioning
confidence: 99%